Postoperative Adjuvant Radiotherapy in Atypical Meningioma Patients: A Meta-Analysis Study - Song, Dengpan; Xu, Dingkang; Han, Hongjie; Gao, Qiang; Zhang, Mingchu; Wang, Fang; Wang, Guoqing; Guo, Fuyou (Frontiers in Oncology, 2021)
Background and Purpose Consensus regarding the need for adjuvant radiotherapy (RT) in patients with atypical meningiomas (AMs) is lacking. We compared the effects of adjuvant RT after surgery, gross total resection (GTR), and subtotal resection (STR) on progression-free survival (PFS) and overall survival (OS) in patients with AMs, respectively. Methods We performed a systematic review and meta-analysis of the literature published in PubMed, Embase, and the Cochrane Library from inception to February 1, 2021, to identify articles comparing the PFS and OS of patients receiving postoperative RT after surgery, GTR and STR. Results We identified 2307 unique studies; 24 articles including 3078 patients met the inclusion criteria. The sensitivity analysis results showed that for patients undergoing undifferentiated surgical resection, adjuvant RT reduced tumor recurrence (HR=0.70, p<0.0001) with no significant effect on survival (HR=0.89, p=0.49). Postoperative RT significantly increased PFS (HR=0.69, p=0.01) and OS (HR=0.55, p=0.007) in patients undergoing GTR. The same improvement was observed in patients undergoing STR plus RT (PFS: HR=0.41, p<0.00001; OS: HR=0.47, p=0.01). A subgroup analysis of RT in patients undergoing GTR showed no change in PFS in patients undergoing Simpson grade I and II resection (HR=1.82, p=0.22) but significant improvement in patients undergoing Simpson grade III resection (HR=0.64, p=0.02). Conclusion Regardless of whether GTR or STR was performed, postoperative RT improved PFS and OS to varying degrees. Especially for patients undergoing Simpson grade III or IV resection, postoperative RT confers the benefits for recurrence and survival.